Intention to adopt Shariah compliant savings scheme among non-Muslim contributors / Wei-Loon Koe and Fara Zawani Nava - Wei, Loon Koe; Nava, Fara Zawani (Universiti Teknologi MARA, Shah Alam, 2019)
Malaysia is an Islamic state which encourages Shariah compliant businesses. Employee Provident Fund (EPF) has initiated a new Shariah compliant savings scheme known as Simpanan Shariah.The scheme is not alien to Muslim members but the factors that develop the interests of non-Muslim members to adopt it is still unknown. Thus, this study examined the factors influencing non-Muslim members' intention to opt for Simpanan Shariah in EPF. The research model was developed based on Theory of Planned Behavior (TPB). The data was collected based on questionnaire survey. From the multiple regressions analysis, it found that governmental support was the most important factor in influencing non-Muslim members' intention to adopt Simpanan Shariah. The next factor was trust and followed by perceived behavioural control. However, attitude and subjective norm did not influence the intention to adopt Simpanan Shariah among the non-Muslim members. This study suggested that there are ample rooms for EPF to further develop Simpanan Shariah. In doing so, EPF could collaborate with government to promote Simpanan Shariah. In addition, EPF also needs to create awareness and provides more information to their non-Muslim members by using their mother-tongue languages. Suggestions to future researchers have also been put forth at the end of this paper.